Nanophotonic control of thermal radiation for energy applications [Invited] - Li, Wei; Fan, Shanhui (Optics express, 2018)
The ability to control thermal radiation is of fundamental importance for a wide range of applications. Nanophotonic structures, where at least one of the structural features are at a wavelength or sub-wavelength scale, can have thermal radiation properties that are drastically different from conventional thermal emitters, and offer exciting opportunities for energy applications. Here we review recent developments of nanophotonic control of thermal radiation, and highlight some exciting energy application opportunities, such as daytime radiative cooling, thermal textile, and thermophotovoltaic systems that are enabled by nanophotonic structures.